2003
DOI: 10.1021/bi020648j
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Spectroscopic Characterization of Half-Liganded Iron−Zinc Hybrid Hemoglobin:  Evidence for Conformational Plasticity within the T State,

Abstract: Functionally distinct conformations of HbA (human adult hemoglobin) were probed using deoxy and diliganded derivatives of symmetric Fe-Zn hybrids of HbA. To expand the range of accessible structures, different environments were utilized including solution, sol-gel encapsulation, and crystals. Further structural and functional modulation was achieved by the addition of allosteric effectors. Functional characterization included oxygen affinity measurements, CO combination rates, and geminate and bimolecular CO r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
77
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(96 citation statements)
references
References 82 publications
19
77
0
Order By: Relevance
“…A structural basis for the linkage between heme reactivity and both effector and ligation-dependent distributions of HT and LT within the T-state can be seen from previous spectroscopic earlier works (20,21,26,62,63). These UV and visible resonance Raman studies on T-state populations with different HT/LT composition show that the highly stable T-state ␣ 1 ␤ 2 interface associated with deoxy-HbA undergoes progressive loosening in going from the extreme LT to HT populations.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A structural basis for the linkage between heme reactivity and both effector and ligation-dependent distributions of HT and LT within the T-state can be seen from previous spectroscopic earlier works (20,21,26,62,63). These UV and visible resonance Raman studies on T-state populations with different HT/LT composition show that the highly stable T-state ␣ 1 ␤ 2 interface associated with deoxy-HbA undergoes progressive loosening in going from the extreme LT to HT populations.…”
Section: Discussionmentioning
confidence: 85%
“…This point is illustrated by the comparison of FeCO/Cr 3ϩ and FeCO/Zn 2ϩ data showing that within the T-state, ligand binding (as mimicked by the Cr 3ϩ ion) biases the HT/LT distribution toward HT with respect to the remaining deoxy sites. The Raman results show that in shifting toward the HT population, proximal strain decreases, which is associated with enhanced ligand reactivity (20,21,27,62). In addition we anticipate that it is also likely that access to the ␤ heme is enhanced due to either a shifting of the Val E11 side chain or to an interface-associated loosening that enhances the amplitude of side chain fluctuations that transiently increase access to the ␤ heme.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13] In addition, tertiary and quaternary conformational changes in heme proteins, such as myoglobin (Mb) and hemoglobin (Hb), can be inhibited or dramatically slowed, which allows these proteins to be "trapped" and studied in non-equilibrium structural conformations. [14][15][16][17][18][19][20][21][22] The origin of the stability imparted by the silica sol-gel matrix is complex. Since the mean pore diameters in aged wet sol-gels (typically <10 nm) are comparable to the diameters of Mb and Hb, the pore walls could physically restrict protein motions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it has been shown that after photolysis of HbCO encapsulated in the T state, both the E and F helices assume intermediate positions with respect to those that characterize the Hb equilibrium states. Moreover, ligand rebinding kinetics of CO to encapsulated Hb were measured in flash photolysis experiments both at room [58,87,89,90,127,[129][130][131][132] and cryogenic temperatures [88]. Inhibition of the quaternary transition allowed to study CO rebinding kinetics to pure T and R states.…”
Section: Trapping Reaction Intermediates: Inhibition Of Conformationamentioning
confidence: 99%